Optical Modeling of Sea Salt Aerosols: The Effects of Nonsphericity and Inhomogeneity. Issue 1 (15th January 2018) - Bi, Lei; Lin, Wushao; Wang, Zheng; Tang, Xiaoyun; Zhang, Xiaoyu; Yi, Bingqi
Abstract: The nonsphericity and inhomogeneity of marine aerosols (sea salts) have not been addressed in pertinent radiative transfer calculations and remote sensing studies. This study investigates the optical properties of nonspherical and inhomogeneous sea salts using invariant imbedding T‐matrix simulations. Dry sea salt aerosols are modeled based on superellipsoidal geometries with a prescribed aspect ratio and roundness parameter. Wet sea salt particles are modeled as coated superellipsoids, as spherical particles with a superellipsoidal core, and as homogeneous spheres depending on the level of relative humidity. Aspect ratio and roundness parameters are found to be critical to interpreting the linear depolarization ratios (LDRs) of NaCl crystals from laboratory measurements. The optimal morphology parameters of NaCl necessary to reproduce the measurements are found to be consistent with data gleaned from an electron micrograph. The LDRs of wet sea salts are computed based on inhomogeneous models and compared with the measured data from ground‐based LiDAR. The dependence of the LDR on relative humidity is explicitly considered. The increase in the LDR with relative humidity at the initial phase of deliquescence is attributed to both the size increase and the inhomogeneity effect. For large humidity values, the LDR substantially decreases because the overall particle shape becomes more spherical and the inhomogeneity effect in a particle on the LDR is suppressed for submicron sea salts. However, the effect of inhomogeneity on optical properties is pronounced for coarse‐mode sea salts. These findings have important implications for atmospheric radiative transfer and remote sensing involving sea salt aerosols. Key Points: Sea salts are modeled as homogeneous and inhomogeneous superellipsoids as a function of relative humidity Nonsphericity and inhomogeneity are shown to be key in interpreting laboratory measurements and LiDAR field observations The effect of inhomogeneity on the asymmetry factor is significant for coarse‐mode sea salt aerosols